Return On Equity Terhadap Kinerja Perbankan Dan Nilai Emas Sebagai Variabel Moderasi - Winarto, Edi; ., Suryadi (STIE Malangkucecwara, 2019)
This study purposes to determine the effect of Return on Equity on banking performance assessed by Tobin's Q through the value of gold, whether direct or indirect influence. This type of research is an explanatory research with a quantitative approach. The population used in this study were 40 banking sector companies listed on the Indonesia Stock Exchange from 2013 to 2018. The sampling technique used purposive sampling so that the chosen sample was 29. This study used descriptive statistical data analysis and part analysis. The results show that ROE is not a significant negative effect while Gold on Q is a significant negative effect, the indirect coefficient is 0.02139 and the Total Effect is -0.02261, it means that the actual relationship is an indirect relationship better affecting Tobin's Q (Banking Performance ) which also means that indirectly the gold value variable can drive influence on Company Performance.